The Etiology of Paralytic Strabismus at an Indonesian Tertiary Hospital from 2017 to 2022 - Azizah, Aulia Rachma Nur; Loebis, Rozalina; Hidayati, Hanik Badriyah; Wahyuni, Indri; Wulandari, Lely Retno (Folia Medica Indonesiana, 2024)
Highlights: 1. This study investigated the etiology of paralytic strabismus, a condition that requires further research to prevent its incidence, particularly in adults. 2. The findings of this study provided valuable insight into the primary etiology of paralytic strabismus and its underlying factors. Abstract Paralytic strabismus is the most common cause of adult-onset strabismus. It can result from paralysis of the third, fourth, or sixth cranial nerves, either separately or in combination, which are responsible for innervating the ocular motor muscles. Paralysis of these cranial nerves occurs due to congenital disorders, neoplasms, trauma, intracranial processes, idiopathic diseases, and other causes. This study aimed to determine the etiology of paralytic strabismus incidence at the Department of Ophthalmology of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, between 2017 and 2022. This study employed a retrospective methodology and utilized total sampling. The medical records of patients diagnosed with paralytic strabismus were used to collect secondary data. Out of the total of 282 cases, the most common condition was combined ocular motor cranial nerve palsy, which accounted for 102 (36.2%) cases. The main factors contributing to this condition were neoplasms (37.2%), intracranial processes (25.5%), trauma (25.5%), other causes (8.8%), idiopathic diseases (2%), and congenital disorders (1%). The incidence of third cranial nerve palsy and sixth cranial nerve palsy was equally prevalent, each accounting for 86 (30.5%) cases. Meanwhile, fourth cranial nerve palsy was the least frequent with just eight (2.8%) cases. This study concluded that the most frequent etiology of paralytic strabismus was combined ocular motor nerve paralysis, which primarily results from neoplasms.